Insecticidal capacity of Cestrum parqui (Solanaceae) leaf extracts on Xanthogaleruca luteola (Coleoptera: Chrysomelidae) adults - Huerta , Amanda; Chiffelle, Ítalo; Araya, Laura; Curkovic, Tomislav; Araya, Jaime (Revista Colombiana de Entomología, 2021)
Among a series of exotic pests that have been reported in Chile, Xanthogaleruca luteola (Coleoptera: Chrysomelidae), a defoliating insect of elms (Ulmus spp.), is causing important damage in urban trees in central Chile. The insecticidal capacity of water and ethanol extracts obtained from new and mature leaves of Cestrum parqui (Solanaceae) was evaluated at various concentrations on X. luteola adults in the laboratory. Bioassays with a completely randomized design were used to analyze the effects of each extract. Also, the mean lethal concentration (LC50) was determined for both mature leaf states and solvents. A proximal analysis was done to determine the physical and chemical differences between the maturity stages. Proximal analysis of the powder of both leaf stages revealed differences (P < 0.01) in the content of humidity, ashes, lipids, and proteins, but not in the raw fiber content nor the non-nitrogenous extract. On the third day after exposure, the order of decreasing effectiveness (LC50) ofthe insecticide extracts was: new-ethanol (2.5 % w/v), new-water (3.8 % w/v), mature-ethanol (6.7 % w/v) and mature-water (9.2 % w/v). Our results suggest that C. parqui leaf extracts may have potential use as a bioinsecticide in integrated pest management plans for the control of X. luteola adults, however, tests at a larger scale are necessary to confirm our results.